2000
DOI: 10.1046/j.1365-246x.2000.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

In search of earthquake precursors in the water-level data of 16 closely clustered wells at Tono, Japan

Abstract: Water‐level data recorded during 1989–1999 at 16 closely clustered wells near the Tono mine in central Japan are searched for possible premonitory changes before earthquakes. The results suggest that some water‐level drops at a sensitive well before an M5.8 local earthquake on 1997 March 16 and some large distant earthquakes during 1994–1995 in Japan may have been premonitory in nature. The high sensitivity of this well to earthquake occurrence is attributed to the near‐critical hydrological conditions and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Some of the pre-earthquake drops were later found to be due to human activities (e.g., drilling of holes by other people across the fault, resulting in a cross-fault water flow), however one of them, beginning about six months before a magnitude 5.8 local earthquake (the largest near Vol. 163, 2006 Earthquake-induced Groundwater 637 the well since 1983) 50 km away in 1997 may be truly premonitory in nature (KING et al, 2000). The sensitivity of the well showed a temporary decrease during a oneyear period after the earthquake, similar to what was observed by WAKITA (1996), presumably due to a temporary relaxation of local stress to a subcritical level, as a result of the magnitude 5.8 earthquake.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Some of the pre-earthquake drops were later found to be due to human activities (e.g., drilling of holes by other people across the fault, resulting in a cross-fault water flow), however one of them, beginning about six months before a magnitude 5.8 local earthquake (the largest near Vol. 163, 2006 Earthquake-induced Groundwater 637 the well since 1983) 50 km away in 1997 may be truly premonitory in nature (KING et al, 2000). The sensitivity of the well showed a temporary decrease during a oneyear period after the earthquake, similar to what was observed by WAKITA (1996), presumably due to a temporary relaxation of local stress to a subcritical level, as a result of the magnitude 5.8 earthquake.…”
Section: Introductionmentioning
confidence: 68%
“…Earlier results, obtained before 1980 mainly in China, observed earlier: (1) Sensitivity of monitoring sites, even only meters apart, can be greatly different; (2) at near-field sites, some recorded earthquake-related changes are approximately consistent with poroelastic dislocation models of earthquakes; (3) however, ''far-field'' co-and postseismic changes recorded for many moderate and large earthquakes at some ''sensitive sites'' are too large (up to about 1000 km or more for magnitude 8) to be explained by the poroelastic models. Being recorded at larger distances for larger earthquakes, they are probably triggered by seismic shaking; (4) the recorded premonitory changes are relatively few and uncertain; (5) sensitive sites are usually located on or near active faults and characterized by some near-critical hydrologic or geochemical condition (e.g., permeability that can be greatly changed by a slight shaking or stress change); (6) the earthquake-related changes recorded for different earthquakes at a sensitive site are usually similar, regardless of the earthquake's location and focal mechanism; and (7) the sensitivity may change with time as the crustal stress changes (e.g., SILVER and VALLETTE-SILVER, 1992;ZHANG, 1994;ROELOFFS, 1988ROELOFFS, , 1996WAKITA, 1996;TOUTAIN and BAUBRON, 1999;KING et al, 1999KING et al, , 2000KING and IGARASHI, 2002;MONTGOMERY and MANGA, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Much research using data obtained from groundwater monitoring has been reported. Examples include groundwater drought evaluation [4][5][6][7], studies of the relationship between climate change and groundwater [8,9], groundwater quality variables [10,11], seawater intrusion [12], and earthquake observation through groundwater analysis [13][14][15][16][17]. When interpreting groundwater monitoring data, fundamental information regarding the hydrogeological characteristics, the groundwater flow system, its fluctuations, and the connectivity of aquifers must be obtained and understood.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the flow process, particularly after small changes, is often impeded by pumping or other hydrologic factors. Preseismic changes are seldom reported KOIZUMI and TSUKUDA, 1999), and the supporting evidence and underlying mechanism of their relations to fault deformation or earthquakes are not clear (KING et al, 2000).…”
Section: Introductionmentioning
confidence: 99%